IoT-based fire and gas alarm for enhanced protection - Sulhan, Muhammad Aiman; Rosli, Muhammad Afiq Hakimi; Md Sin, Nor Diyana (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
This technical report documents the design and simulation of an Internet of Things (IoT)- Based Fire and Gas Alarm for Enhanced Protection for Efficient Emergency Response utilizing ESP32-based sensors and connect to mobile phone. The system incorporates a Fire Sensor, DHT11 Temperature Sensor, and a MQ2 Gas sensor, complemented by a Liquid Crystal Display (LCD) for real-time data visualization. The inclusion of a Wi-Fi module enhances the system's capabilities, transforming it into an Internet of Things (IoT) device capable of receiving notification about the alarm system. Additionally, a fire alarm has been integrated as one of the systems to detect only fire and temperature. Leveraging Tinkercad’s simulation platform, the ESP32 microcontroller processes data from these sensors to monitor and manage critical parameters in the house. Responsive components, including LEDs for visual alerts and a buzzer for connecting the sensor, enhance the system's functionality. The Arduino code incorporates intelligent decision-making, dynamically controlling them, activating LEDs and buzzer based on predefined temperature, fire, and gas sensor conditions, and interfacing with the Wi-Fi module for connectivity to the user’s phone. The LCD displays various information screens to alert people on what danger they are facing off. This IoT-Integrated Next-Gen Fire and Gas Alarm System serves as a versatile and scalable solution to automated censoring the conditions of surrounding area than can lead to a fire issue with the added capability of IoT connectivity for efficient emergency response